High-salt oil-containing sewage demulsifier and preparation method thereof

CN122940923APending Publication Date: 2026-10-20GUANGDONG SHANMEI ENVIRONMENTAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611032978.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

1、采用以多糖分子链为骨架并同时接枝两性离子基团、疏水识别链段和多酚锚定结构的破乳剂后,破乳过程由单一电荷中和转变为同一分子链上的多位点协同作用。两性离子基团中的季铵盐结构与磺酸盐结构或羧酸盐结构共同存在,使破乳剂在高盐水相中保持水化分散状态,减少盐析和自聚集;疏水识别链段由脂肪族烃链或植物油基烃链构成,可与油滴表面的石油类有机物发生亲油结合,使多糖接枝共聚物进入油水界面;多酚锚定结构中的邻二酚结构、没食子酰结构或单宁酸残基可与胶质、沥青质及金属离子关联的界面组分形成多点结合。上述结构连接在同一多糖骨架上,使水相稳定、界面插入、界面锚定和分子链桥联在同一破乳过程中连续发生,被复合界面膜包覆的细小油滴由稳定分散状态转为可聚并状态。破乳后油层和水层边界更清楚,水相中乳化油、胶体油和悬浮油残留减少,浑浊界面层厚度降低,水相中细小油珠继续分散的现象减少,后续分离单元接收的进水含油形态由乳化分散状态转为较易截留的聚并状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of wastewater treatment and water treatment agents, and discloses a demulsifier for high-salt, oily wastewater and its preparation method. The demulsifier comprises a polysaccharide graft copolymer with a polysaccharide molecular chain as its backbone, wherein the polysaccharide molecular chain is simultaneously grafted with zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures. Its preparation method includes polysaccharide swelling and activation, zwitterionic monomer grafting, hydrophobic monomer grafting, polyphenol compound grafting, purification, and formulation treatment. This demulsifier can maintain a dispersed state in a high-salt water phase, enter the oil-water interface, weaken the complex interfacial film, promote the aggregation and separation of emulsified oil droplets, and reduce residual oil in the aqueous phase and the interfacial turbidity layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment and water treatment agents, and discloses a demulsifier for high-salt and oily wastewater and its preparation method. Background Technology

[0002] High-salt, oily wastewater mainly originates from oilfield produced water, refining unit drainage, oily cleaning wastewater, fracturing flowback fluid, and some chemical saline wastewater. This type of wastewater contains petroleum-based organic matter, surfactants, calcium and magnesium salts, sodium salts, chloride ions, fine solid particles, and colloidal organic matter. During transportation, shearing, chemical dosing, reinjection, and cleaning, the oil phase is dispersed into fine oil droplets. The surface of these droplets is covered by natural colloids, asphaltenes, residual additives, and inorganic particles, forming an interfacial film with charge repulsion and steric hindrance. Existing water treatment processes typically adjust the pH and temperature first, then add demulsifiers or coagulants to destabilize the emulsified oil before it enters oil-water separation, flotation, sedimentation, filtration, or pre-biological treatment units. The key to conventional treatment is to weaken the oil-water interface film and promote the aggregation of small oil droplets. However, high-salt systems can compress the double layer, change the hydration state of the reagent and the interfacial adsorption behavior, and also allow polyvalent metal ions to participate in the connection of oil droplet surface colloids and particles, thus limiting the demulsification pathways available in ordinary oily wastewater in this type of wastewater.

[0003] Currently, most conventional technical solutions employ polyether demulsifiers, quaternary ammonium cationic polymers, phenolic amine resin demulsifiers, or inorganic aluminum-iron salt coagulants. Polyether demulsifiers rely on their hydrophilic and lipophilic segments to spread at the oil-water interface, displacing the original emulsifier and reducing the interfacial film strength. Cationic polymers neutralize the charge, compressing the electric double layer of oil droplets and promoting the formation of flocs from oil droplets and suspended particles through molecular chain bridging. Phenolic amine resin demulsifiers rely on their aromatic and amine structures to competitively adsorb colloids and asphaltenes at the interface. Inorganic salt coagulants remove emulsified oil through the adsorption, sweeping, and sedimentation of hydrolysis products. These agents are typically added to the reaction tank as single agents or in combination, and oil-water separation is achieved through rapid mixing, slow stirring, and settling to achieve stratification. In low- or medium-salinity wastewater, this process can form an oil layer and flocculated sediments; in high-salinity wastewater, the reagent is prone to chain segment curling, precipitation, excessive flocculation or insufficient interfacial replacement, and the aqueous phase still carries emulsified oil after demulsification, and the stratification interface often presents a state of floc suspension and oil droplet back-mixing.

[0004] To improve demulsification stability in high-salt environments, existing technologies have explored the use of bio-based polymers such as natural polysaccharides, modified starch, chitosan, and cellulose derivatives in oily wastewater treatment. These materials contain hydroxyl, amino, or carboxyl groups on their molecular chains, enabling them to capture oil droplets through adsorption and bridging, and exhibit good aqueous compatibility. Some schemes further introduce cationic groups or hydrophobic alkyl segments to enhance charge neutralization or lipophilic interface recognition capabilities. While these modified polysaccharides possess some demulsification ability in common emulsified oily wastewater, their functional units are often relatively simple. Introducing only cationic groups makes them susceptible to shielding by high-concentration salt ions, causing the molecular chains to transition from an extended to a contracted state in saline water. Introducing only hydrophobic segments leads to aqueous phase aggregation before and after addition, resulting in insufficient molecules entering the oil droplet interface. Relying solely on polysaccharide bridging has a weak ability to disrupt the dense interfacial film formed by colloids, asphaltenes, and inorganic ions; even after oil droplets are captured, they may retain their emulsified structure, making it difficult for small oil droplets to continuously coalesce.

[0005] The main technical problem in the existing demulsification treatment of high-salt oily wastewater is that demulsifiers, in the presence of high concentrations of inorganic salts, struggle to simultaneously maintain aqueous phase dispersion stability, oil-water interface migration capability, and the ability to disrupt the complex interfacial film. This leads to conformational contraction, salting-out aggregation, or weakened activity due to the aqueous ionic environment before the agent fully reaches the oil droplet interface. Furthermore, molecules that do enter the interface are unable to disrupt the protective film composed of surfactants, colloids, asphaltenes, metal ions, and fine particles. This protective film maintains spatial stability of oil droplets even after electrical shielding has occurred; simple charge neutralization or simple hydrophobic insertion cannot form sustained aggregation. Adding excessive amounts of agent can also cause redispersion of the emulsion or interfacial turbidity. Therefore, the core problem to be solved is to construct a demulsifier that is stable in a high-salt water phase, can directionally enter the oil-water interface, and simultaneously weakens the organic colloid film and the inorganic ion complex film, enabling emulsified oil droplets to transition from a stable interfacial film state to a coalesced and separated state. Summary of the Invention

[0006] To address the shortcomings of existing high-salt oily wastewater demulsifiers in maintaining aqueous phase dispersion stability, oil-water interface migration ability, and composite interfacial film destruction ability simultaneously in the presence of high concentrations of inorganic salts, this invention provides a high-salt oily wastewater demulsifier and its preparation method, enabling the demulsifier to exist stably in a high-salt water phase and enter the oil-water interface to weaken the composite interfacial film formed by organic colloids, asphaltenes, metal ions, and fine particles.

[0007] To address the aforementioned technical problems, this invention provides a demulsifier for high-salt, oily wastewater, comprising a polysaccharide graft copolymer. The polysaccharide graft copolymer uses a polysaccharide molecular chain as its backbone, and the polysaccharide molecular chain is simultaneously grafted with zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures. The zwitterionic groups include sulfobetaine groups, carboxybetaine groups, or quaternary ammonium salt-carboxylate complex groups. The hydrophobic recognition segments include aliphatic hydrocarbon chains or vegetable oil-based hydrocarbon chains. The polyphenol anchoring structures include ortho-diol structures, galloyl structures, or tannic acid residues.

[0008] The polysaccharide molecular chain possesses a hydrophilic framework and a bridging structure in the aqueous phase, serving as a common carrier for the zwitterionic groups, the hydrophobic recognition segments, and the polyphenol anchoring structure. The zwitterionic groups maintain the hydration state of the molecular chain in the high-salt water phase, reducing chain segment contraction and aggregation caused by inorganic salts. The hydrophobic recognition segments bind lipophilically to petroleum-based organic matter, colloids, and hydrophobic components on the oil droplet surface, causing the polysaccharide graft copolymer to migrate towards the oil-water interface. The polyphenol anchoring structure binds at multiple points to interfacial components associated with colloids, asphaltenes, and metal ions through phenolic hydroxyl groups, disturbing the original interfacial film arrangement. These three types of grafting structures are located on the same polysaccharide molecular chain, allowing aqueous phase dispersion, interfacial insertion, interfacial anchoring, and polysaccharide bridging to occur continuously within the same molecular system, thereby transforming the fine emulsified oil droplets in high-salt, oily wastewater from a stable coated state to a polymerizable and separable state.

[0009] Furthermore, in the above technical solution, the polysaccharide molecular chain is derived from at least one of chitosan, carboxymethyl cellulose, alginate, and starch derivatives. The polysaccharide molecular chain retains at least one of the reaction sites of hydroxyl, amino, or carboxyl groups. The zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures are grafted onto the reaction sites through ether bonds, amide bonds, ester bonds, or quaternization linkage structures, respectively.

[0010] In specific implementations, chitosan, carboxymethyl cellulose, alginate, and starch derivatives all possess a polysaccharide backbone structure. The hydroxyl, amino, or carboxyl groups provide a grafting basis, allowing the zwitterionic groups, the hydrophobic recognition segments, and the polyphenol anchoring structure to be fixed on the same molecular chain through stable linkages. The ether, amide, ester, or quaternization linkages ensure that the functional units are not dispersed as free small molecules during addition and mixing, but rather migrate synchronously with the polysaccharide molecular chains to the aqueous phase and oil-water interface, reducing the concentration of effects caused by functional unit separation.

[0011] Furthermore, in the above technical solution, the zwitterionic group includes a cation center and an anion center in the same side-linked branch structure, the cation center is a quaternary ammonium salt structure, the anion center is a sulfonate structure or a carboxylate structure, and a spacer segment containing a hydroxyl group or an ether oxygen is provided between the zwitterionic group and the polysaccharide molecular chain.

[0012] In specific implementations, the quaternary ammonium salt structure and the sulfonate or carboxylate structure are located in the same side-linked branch structure, enabling the zwitterionic group to simultaneously possess both cationic and anionic centers. In a high-salt water phase, the zwitterionic group can form a hydration layer and buffer the influence of external salt ions on the conformation of the polysaccharide graft copolymer. The spacer segments containing hydroxyl or ether oxygen are located between the zwitterionic group and the polysaccharide molecular chain, which can increase the flexibility and hydration capacity of the side chain, keeping the zwitterionic group exposed in the aqueous phase and preventing it from being shielded by the polysaccharide molecular chain.

[0013] Furthermore, in the above technical solution, the hydrophobic recognition segment is formed by fatty alcohol glycidyl ether residues, alkylamine residues, fatty acid acyl residues or epoxidized vegetable oil ring-opening residues. The hydrophobic recognition segment and the zwitterionic group are distributed on the same polysaccharide molecular chain, and a grafting structure is formed by alternating hydrophilic and hydrophobic segments through the polysaccharide molecular chain.

[0014] In specific implementations, the fatty alcohol glycidyl ether residues, alkylamine residues, fatty acid acyl residues, or epoxidized vegetable oil ring-opening residues can form lipophilic side chains, giving the polysaccharide graft copolymer a structural basis for recognizing hydrophobic components at the oil droplet interface. The hydrophobic recognition segments and the zwitterionic groups are distributed on the same polysaccharide molecular chain, allowing the same molecule to simultaneously possess both salt water dispersibility and oil phase affinity. With alternating connections of hydrophilic and hydrophobic segments, the polysaccharide graft copolymer is less prone to losing its dispersibility in high-salt water phases due to the aggregation of a single hydrophobic segment, and can simultaneously form insertion and spreading structures at the oil-water interface.

[0015] Furthermore, in the above technical solution, the polyphenol anchoring structure is formed by grafting tannic acid, gallic acid, catechol derivatives or dopamine derivatives, the polyphenol anchoring structure contains adjacent phenolic hydroxyl groups or multiple phenolic hydroxyl groups, and the polyphenol anchoring structure and the hydrophobic recognition segment are located together in the side chain region of the polysaccharide molecule chain.

[0016] In specific implementations, the adjacent phenolic hydroxyl groups or polyphenolic hydroxyl groups can undergo hydrogen bonding, complexation, or multi-point adsorption with the colloidal, asphaltenes, and metal ion-related components at the oil droplet interface. The polyphenol anchoring structure and the hydrophobic recognition segment are both located in the side chain region of the polysaccharide molecular chain. This allows the polyphenol anchoring structure to contact the polar and aromatic components in the interfacial film at adjacent spatial positions after the hydrophobic recognition segment is inserted into the oil droplet interface, reducing the problem of insufficient interfacial anchoring after a single hydrophobic insertion.

[0017] Furthermore, in the above technical solution, the polysaccharide molecular chain is a modified polysaccharide molecular chain formed by carboxymethylation, hydroxypropylation, amination or oxidation treatment. The modified polysaccharide molecular chain is provided with a first grafting site, a second grafting site and a third grafting site, respectively. The first grafting site is connected to the zwitterionic group, the second grafting site is connected to the hydrophobic recognition segment, and the third grafting site is connected to the polyphenol anchoring structure.

[0018] In specific implementations, the carboxymethylation, hydroxypropylation, amination, or oxidation treatments can form modified structures suitable for subsequent grafting on the polysaccharide molecular chain. The first, second, and third grafting sites are used to connect different functional units, so that the zwitterionic groups, the hydrophobic recognition segments, and the polyphenol anchoring structures are clearly distributed on the modified polysaccharide molecular chain. This site-specific grafting method allows each functional structure to function independently of random mixing, but rather to synergistically participate in aqueous phase dispersion, interfacial migration, and interfacial film disturbance along the same modified polysaccharide molecular chain.

[0019] Furthermore, in the above technical solution, the spacer segment containing hydroxyl or ether oxygen is formed by glycidyl, hydroxypropyl, polyether short chain or hydroxyalkyl segment, one end of the spacer segment is connected to the polysaccharide molecular chain, and the other end is connected to the quaternary ammonium salt structure, and the sulfonate structure or carboxylate structure is connected to the quaternary ammonium salt structure through alkyl linking chain.

[0020] In specific implementations, the glycidyl group, hydroxypropyl group, polyether short chain, or hydroxyalkyl segment contains hydrophilic atoms or hydrophilic groups, which can improve the hydration degree around the zwitterionic group. The spacer segment draws the quaternary ammonium salt structure out from near the main chain of the polysaccharide molecule, giving the quaternary ammonium salt structure better spatial accessibility; the sulfonate structure or carboxylate structure is connected to the quaternary ammonium salt structure through the alkyl linking chain, so that the cation center and the anion center maintain structural association within the same side chain, thereby maintaining the conformational stability of the zwitterionic group in the high-salt water phase.

[0021] Furthermore, in the above technical solution, the hydrophobic recognition segment comprises at least one of straight-chain alkyl, branched alkyl, fatty acid unsaturated hydrocarbon chain or vegetable oil-based fatty chain, and the hydrophobic recognition segment is grafted onto the polysaccharide molecular chain through an epoxy ring-opening, amidation or esterification linkage structure, wherein the grafted structure simultaneously retains hydroxyl or ether oxygen linkage units.

[0022] In specific implementations, the straight-chain alkyl, branched alkyl, fatty acid unsaturated hydrocarbon chains, or vegetable oil-based fatty acid chains can compatibly bind with the hydrophobic components at the oil droplet interface, giving the polysaccharide graft copolymer a structural basis for entering the oil-water interface. The epoxy ring-opening, amidation, or esterification linkage structure fixes the hydrophobic recognition segment to the polysaccharide molecular chain, preventing it from precipitating as a free hydrophobic component. The hydroxyl or ether oxygen linkage unit is retained in the graft structure, ensuring that the hydrophobic recognition segment still has a certain hydrophilic linkage region around it, reducing the adverse effects of excessive aggregation of hydrophobic segments on aqueous phase dispersion.

[0023] Furthermore, in the above technical solution, the polyphenol anchoring structure is connected to the polysaccharide molecular chain through amidation, Schiff base reduction, esterification or oxidative coupling, and the hydrophobic recognition segment or polysaccharide backbone segment is disposed between the polyphenol anchoring structure and the zwitterionic group, and the polyphenol anchoring structure does not completely block the hydroxyl, amino or carboxyl groups on the polysaccharide molecular chain.

[0024] In specific implementations, amidation, Schiff base reduction, esterification, or oxidative coupling can connect the polyphenol anchoring structure to the polysaccharide molecular chain, allowing it to function together with the polysaccharide graft copolymer near the oil-water interface. The polyphenol anchoring structure and the zwitterionic groups are spaced apart by the hydrophobic recognition segments or polysaccharide backbone fragments, reducing mutual occlusion of the two types of functional groups in the same spatial location. The polyphenol anchoring structure does not completely block the hydroxyl, amino, or carboxyl groups on the polysaccharide molecular chain, allowing the polysaccharide molecular chain to retain the reaction sites or hydrophilic sites required for hydration, contact, and bridging.

[0025] In addition, to prepare the above-mentioned high-salt oily wastewater demulsifier, the present invention also provides a method for preparing the high-salt oily wastewater demulsifier, comprising: swelling and activating a polysaccharide raw material to obtain a polysaccharide molecular chain containing reaction sites; grafting an amphoteric monomer onto the polysaccharide molecular chain to form an amphoteric polysaccharide intermediate; grafting a hydrophobic monomer onto the amphoteric polysaccharide intermediate to form a hydrophobically modified polysaccharide intermediate; grafting a polyphenolic compound onto the hydrophobically modified polysaccharide intermediate; and purifying and formulating the intermediate to obtain the high-salt oily wastewater demulsifier.

[0026] In specific implementation, the preparation method uses the swelling and activation of the polysaccharide raw material as the grafting basis, so that the reaction sites on the polysaccharide molecular chain are in a reactive state. The zwitterionic monomer is first grafted onto the polysaccharide molecular chain to form the zwitterionic polysaccharide intermediate with an aqueous phase dispersion basis; the hydrophobic monomer is then grafted onto the zwitterionic polysaccharide intermediate, so that the resulting hydrophobically modified polysaccharide intermediate has both a salt water dispersion structure and an oil phase recognition structure; after the polyphenol compound is grafted onto the hydrophobically modified polysaccharide intermediate, the zwitterionic group, the hydrophobic recognition segment, and the polyphenol anchoring structure are formed on the same polysaccharide molecular chain. The purification and formulation treatment is used to obtain a demulsifier form that can be added and used, so that the high-salt oily wastewater demulsifier can participate in the demulsification process of high-salt oily wastewater with the polysaccharide graft copolymer as the main component when applied.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By employing a demulsifier with a polysaccharide molecular chain as the backbone and simultaneously grafted with zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures, the demulsification process transforms from single charge neutralization to a multi-site synergistic effect on the same molecular chain. The coexistence of quaternary ammonium salt structures with sulfonate or carboxylate structures in the zwitterionic groups maintains the demulsifier in a hydrated and dispersed state in a high-salt water phase, reducing salting out and self-aggregation. The hydrophobic recognition segments, composed of aliphatic hydrocarbon chains or vegetable oil-based hydrocarbon chains, can undergo lipophilic binding with petroleum-based organic matter on the surface of oil droplets, allowing the polysaccharide graft copolymer to enter the oil-water interface. The ortho-diol, galloyl, or tannic acid residues in the polyphenol anchoring structure can form multi-site bonds with interfacial components associated with colloids, asphaltenes, and metal ions. These structures are connected to the same polysaccharide backbone, enabling aqueous phase stabilization, interfacial insertion, interfacial anchoring, and molecular chain bridging to occur continuously in the same demulsification process. The fine oil droplets coated by the composite interfacial film transform from a stable dispersed state to a coalescing state. After demulsification, the boundary between the oil layer and the water layer becomes clearer, the residual emulsified oil, colloidal oil and suspended oil in the aqueous phase decreases, the thickness of the turbid interface layer decreases, the phenomenon of fine oil droplets continuing to disperse in the aqueous phase decreases, and the oil-containing form of the feed water received by the subsequent separation unit changes from an emulsified and dispersed state to a more easily intercepted aggregated state.

[0028] 2. This demulsifier uses polysaccharide molecular chains as its main structure, retaining reactive sites such as hydroxyl, amino, or carboxyl groups on the molecular chains. These sites can be linked to zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures, respectively. This allows each functional unit to be covalently fixed to the same polymer carrier, rather than simply mixed in the aqueous phase. The zwitterionic groups and hydrophobic recognition segments form a grafted structure on the polysaccharide chain with alternating hydrophilic and hydrophobic regions, reducing aqueous phase aggregation caused by hydrophobic modification alone. The polyphenol anchoring structure and the hydrophobic recognition segments are located together in the side chain region, increasing their contact opportunities with the oil droplet interface film. Unclosed hydroxyl, amino, or carboxyl groups can still participate in hydration and bridging. The preparation method employs a continuous route of polysaccharide swelling and activation, zwitterionicization, hydrophobic modification, polyphenol grafting, purification, and formulation. The resulting product has a clear compositional relationship, reducing the amount of free small molecules and unreacted monomers entering the wastewater system. Compared with demulsification methods that rely on inorganic salt precipitation, this composition does not use hydrolysis precipitation sweeping as the main destabilization path. After demulsification, less inorganic sediment is introduced, and the floc composition is more inclined to oil droplet aggregates and polysaccharide bridges. The load of subsequent sedimentation, filtration and biochemical pretreatment is reduced, the adhesion layer formed by fine emulsified oil on the surface of the filter media is reduced, and the backmixing tendency of residual flocs in the aqueous phase is reduced. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to embodiments. Those skilled in the art can reproduce the technical solution of the present invention and achieve its claimed technical effects based on the content disclosed in this specification. It should be noted that the following embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention. Any non-substantial improvements and adjustments made based on the core concept of the present invention should fall within the scope of protection of the present invention.

[0030] Example 1: This example is the optimal embodiment of a demulsifier for high-salt, oily wastewater. By weight, 100 parts of carboxymethyl chitosan were used as the polysaccharide raw material, 60 parts of glycidyl sulfobetaine as the zwitterionic monomer, 22 parts of dodecyl glycidyl ether as the hydrophobic monomer, and 16 parts of gallic acid as the polyphenol compound. In preparation, carboxymethyl chitosan was added to deionized water, controlling the mass ratio of carboxymethyl chitosan to deionized water to be 1:30. The mixture was stirred and swollen at 40°C for 2 hours to allow the polysaccharide molecular chains to fully extend and expose the hydroxyl, amino, and carboxyl reaction sites. The pH of the system was adjusted to 8.0, and glycidyl sulfobetaine was added. The mixture was reacted at 55°C for 6 hours to allow the zwitterionic groups to be grafted onto the polysaccharide molecular chains via epoxy ring-opening, obtaining a zwitterionic polysaccharide intermediate. Dodecyl glycidyl ether was pre-dispersed in ethanol and then added dropwise to the zwitterionic polysaccharide intermediate. The pH of the system was adjusted to 8.5. A hydrophobically modified polysaccharide intermediate was obtained by reacting at 55°C for 5 hours to graft aliphatic hydrocarbon chains onto polysaccharide molecular chains via epoxy ring-opening. Gallic acid, carbodiimide condensing agents, and hydroxysuccinimide were dissolved in a small amount of deionized water, and the pH was adjusted to 5.5 before adding the hydrophobically modified polysaccharide intermediate. The reaction was carried out at 35°C in the dark for 4 hours to link galloyl structures to the polysaccharide molecular chains via amidation or esterification. After the reaction, the mixture was precipitated with ethanol, and the precipitate was collected by centrifugation, then reconstituted with deionized water. Free small molecules and salt byproducts were removed by dialysis, and the mixture was concentrated and spray-dried to obtain a demulsifier for high-salt oily wastewater. The obtained demulsifier is a polysaccharide graft copolymer, wherein the polysaccharide molecular chains simultaneously possess sulfobetaine groups, dodecyl hydrophobic recognition segments, and galloyl polyphenol anchoring structures.

[0031] Example 2: This example investigates the effect of changes in the type of zwitterionic groups on the performance of the demulsifier. By weight, 100 parts of carboxymethyl chitosan, 60 parts of glycidyl carboxybetaine, 22 parts of dodecyl glycidyl ether, and 16 parts of gallic acid were prepared. The preparation method was the same as in Example 1, except that glycidyl sulfobetaine in Example 1 was replaced with glycidyl carboxybetaine, changing the zwitterionic groups grafted onto the polysaccharide molecular chain from sulfobetaine groups to carboxybetaine groups. The remaining raw material amounts, swelling and activation conditions, hydrophobic grafting conditions, polyphenol grafting conditions, purification methods, and formulation methods were all the same as in Example 1.

[0032] Example 3: This example investigates the effect of varying zwitterionic monomer dosage on demulsifier performance. By weight, 100 parts carboxymethyl chitosan, 45 parts glycidyl sulfobetaine, 22 parts dodecyl glycidyl ether, and 16 parts gallic acid were used. The preparation method was the same as in Example 1, except that the glycidyl sulfobetaine was adjusted from 60 parts to 45 parts to reduce the grafting level of zwitterionic groups on the polysaccharide molecular chain. The other raw material types, hydrophobic recognition segments, polyphenol anchoring structure, and preparation steps were the same as in Example 1.

[0033] Example 4: This example investigates the effect of changes in the type of hydrophobic recognition segment on the performance of the demulsifier. By weight, 100 parts of carboxymethyl chitosan, 60 parts of glycidyl sulfobetaine, 22 parts of octyl glycidyl ether, and 16 parts of gallic acid were prepared. The preparation method was the same as in Example 1, except that dodecyl glycidyl ether was replaced with octyl glycidyl ether, changing the hydrophobic recognition segment grafted onto the polysaccharide molecule from a dodecyl segment to an octyl segment. All other conditions were the same as in Example 1.

[0034] Example 5: This example examines the applicability of vegetable oil-based hydrocarbon chains as hydrophobic recognition segments. By weight, 100 parts carboxymethyl chitosan, 60 parts glycidyl sulfobetaine, 22 parts epoxidized vegetable oil, and 16 parts gallic acid were prepared. The preparation method was the same as in Example 1, except that dodecyl glycidyl ether was replaced with epoxidized vegetable oil, changing the hydrophobic recognition segment from an aliphatic straight-chain hydrocarbon chain to a vegetable oil-based hydrocarbon chain. The epoxidized vegetable oil was grafted onto the polysaccharide molecular chain via a ring-opening reaction. All other conditions were the same as in Example 1.

[0035] Example 6: This example investigates the effect of changes in the type of polyphenol anchoring structure on the performance of the demulsifier. By weight, 100 parts of carboxymethyl chitosan, 60 parts of glycidyl sulfobetaine, 22 parts of dodecyl glycidyl ether, and 16 parts of tannic acid were prepared. The preparation method was the same as in Example 1, except that gallic acid was replaced with tannic acid, changing the polyphenol anchoring structure grafted onto the polysaccharide molecular chain from a galloyl structure to a tannic acid residue. All other conditions were the same as in Example 1.

[0036] Example 7: This example investigates the effect of changes in the source of polysaccharide molecular chains on the performance of demulsifiers. By weight, 100 parts of hydroxypropyl chitosan, 60 parts of glycidyl sulfobetaine, 22 parts of dodecyl glycidyl ether, and 16 parts of gallic acid were prepared. The preparation method was the same as in Example 1, except that carboxymethyl chitosan was replaced with hydroxypropyl chitosan, which altered the distribution of hydrophilic side groups and reactive sites in the polysaccharide backbone. All other conditions, including zwitterionic grafting, hydrophobic grafting, polyphenol grafting, purification, and formulation, remained the same as in Example 1.

[0037] Example 8: This example is used to investigate the applicability of the preparation method to changes in polysaccharide swelling and activation time. The formulation composition and preparation method are the same as in Example 1, except that the swelling and activation time of carboxymethyl chitosan at 40°C is adjusted from 2 hours to 3 hours. The other zwitterionic grafting, hydrophobic grafting, polyphenol grafting, purification and formulation conditions are the same as in Example 1.

[0038] Example 9: This example is used to investigate the applicability of the preparation method to the temperature change of zwitterionic grafting. The formulation and preparation method are the same as in Example 1, except that the glycidyl sulfobetaine grafting reaction temperature is adjusted from 55°C to 50°C, while the reaction time remains 6 hours. All other conditions are the same as in Example 1.

[0039] Example 10: This example is used to investigate the applicability of the preparation method to changes in the pH value of polyphenol grafting. The formulation and preparation method are the same as in Example 1, except that the pH value in the gallic acid grafting step is adjusted from 5.5 to 5.0, while the reaction temperature and reaction time remain unchanged. All other conditions are the same as in Example 1.

[0040] Comparative Example 1: This comparative example is a comparative example lacking the polyphenol anchoring structure. By weight, 100 parts of carboxymethyl chitosan, 60 parts of glycidyl sulfobetaine, and 22 parts of dodecyl glycidyl ether were used, without adding gallic acid. During preparation, polysaccharide swelling activation, zwitterionic grafting, and hydrophobic grafting were performed according to Example 1. After hydrophobic modification, ethanol precipitation, reconstitution, dialysis, concentration, and spray drying were performed directly. Except for the absence of polyphenol grafting, the other conditions were the same as in Example 1.

[0041] Comparative Example 2: This comparative example uses a conventional demulsifier. A fatty alcohol polyether demulsifier was used as the treatment agent, and no polysaccharide graft copolymer preparation was performed. During the demulsification test, the dosage of the fatty alcohol polyether demulsifier, the stirring method, the reaction temperature, the settling time, and the composition of the test wastewater were all the same as those for the demulsifier obtained in Example 1.

[0042] Comparative Example 3: This comparative example is a comparison example where the zwitterionic grafting temperature deviates from the suitable preparation conditions. The formulation and preparation method are the same as in Example 1, except that the glycidyl sulfobetaine grafting reaction temperature is adjusted from 55°C to 90°C, while the reaction time remains 6 hours. All other conditions are the same as in Example 1.

[0043] Comparative Example 4: This comparative example omits the polysaccharide swelling and activation step. The formulation composition is the same as in Example 1. Instead of the 40°C swelling and activation treatment of carboxymethyl chitosan, carboxymethyl chitosan was directly dispersed in deionized water, and glycidyl sulfobetaine was added for grafting reaction. The other zwitterionic grafting, hydrophobic grafting, polyphenol grafting, purification, and formulation conditions are the same as in Example 1.

[0044] Test method: The high-salt, oily wastewater used in the test was prepared from the same batch of simulated wastewater.

[0045] Each liter of simulated wastewater contains 1000 mg of mixed petroleum oil, 50000 mg of sodium chloride, 3000 mg of calcium chloride, 1500 mg of magnesium chloride, 80 mg of sodium dodecylbenzenesulfonate, and 200 mg of suspended kaolin particles. After high-speed shear emulsification, it is left to stand for 2 hours for later use.

[0046] In each example and comparative example, the demulsifier was added to the simulated wastewater at the same dosage, stirred rapidly at 45°C for 2 minutes, then stirred slowly for 10 minutes, and then allowed to stand for 30 minutes.

[0047] The residual petroleum content, oil removal rate, water phase turbidity, oil-water interface clarity time, and interface turbidity layer thickness were measured from samples taken from the middle of the aquifer.

[0048] The residual petroleum content was determined by infrared spectroscopy after petroleum ether extraction. The turbidity of the aqueous phase was measured using a turbidity meter. The time for the oil-water interface to become clear is determined by the stable separation of the oil layer, water layer and interface layer that can be seen with the naked eye. The thickness of the interface turbidity layer is measured by the thickness of the emulsion transition layer after standing for 30 minutes.

[0049] The test results are shown in Table 1.

[0050] Table 1 Performance test results of each embodiment and comparative example

[0051] Results analysis: The demulsifier obtained in Example 1 simultaneously possesses a sulfobetaine group, a dodecyl hydrophobic recognition segment, and a galloyl polyphenol anchoring structure on the same polysaccharide molecular chain. The sulfobetaine group maintains the hydration and dispersion of the polysaccharide graft copolymer in the high-salt water phase. The dodecyl hydrophobic recognition segment can enter the hydrophobic organic layer on the oil droplet surface. The galloyl structure can form multi-point bonds with interfacial components associated with gums, asphaltenes, and metal ions. The polysaccharide backbone provides the basis for molecular chain bridging. These structures form a continuous action pathway within the same molecule. Therefore, the residual petroleum content in the aqueous phase of Example 1 was 31 mg / L, the oil-water interface clearing time was 8 minutes, and the interfacial turbidity layer thickness was 1.5 mm, indicating that aqueous phase dispersion, interfacial migration, and interfacial film disturbance can be completed simultaneously under high-salt conditions.

[0052] In Example 2, after replacing the sulfobetaine group with a carboxybetaine group, the zwitterionic structure, hydrophobic recognition segment, and polyphenol anchoring structure were still retained. The residual petroleum content in the aqueous phase was 45 mg / L, and the oil removal rate was 95.5%. This result indicates that the coexistence of cationic and anionic centers in the zwitterionic group can maintain the dispersion state of the demulsifier in a high-salt water phase. Compared with Example 1, the interface clearing time in Example 2 was extended to 11 minutes, indicating that different anionic centers affect the hydration state and interface migration rate in the high-salt system, but do not change the overall demulsification path.

[0053] In Example 3, reducing the amount of glycidyl sulfobetaine resulted in a decrease in the number of zwitterionic groups on the polysaccharide molecular chain, an increase in the residual petroleum content in the aqueous phase to 58 mg / L, and an increase in the turbidity of the aqueous phase to 31 turbidity units. This result indicates that retaining sufficient zwitterionic graft structures on the same polysaccharide backbone is beneficial in reducing molecular chain shrinkage and local aggregation caused by a high-salt ion environment. While the number of zwitterionic groups decreased, the hydrophobic recognition segments and polyphenol anchoring structures could still participate in interfacial interactions, but the number of demulsifier molecules reaching the oil-water interface decreased, leading to a reduction in the aggregation of fine emulsion droplets.

[0054] In Example 4, after replacing the dodecyl segment with the octyl segment, the residual petroleum content in the aqueous phase was 63 mg / L, and the thickness of the interfacial turbidity layer was 3.0 mm. This result indicates that the carbon chain structure of the hydrophobic recognition segment affects the binding strength between the demulsifier and the petroleum-based organic matter on the oil droplet surface. The octyl segment, still belonging to an aliphatic hydrocarbon chain, can provide lipophilic recognition ability, but its interfacial insertion ability is weaker than that of the dodecyl segment in Example 1, thus reducing the oil droplet coalescence rate and the degree of interfacial clarification.

[0055] In Example 5, after replacing the dodecyl segment with a vegetable oil-based hydrocarbon chain, the residual petroleum content in the aqueous phase was 40 mg / L, and the oil-water interface clearing time was 10 minutes. The vegetable oil-based hydrocarbon chain, through epoxy ring-opening grafting to the polysaccharide molecular chain, provides a hydrophobic side chain compatible with the oil phase and participates in demulsification together with zwitterionic groups and polyphenol anchoring structures. This result demonstrates that the hydrophobic recognition segment is not limited to a single straight-chain alkyl structure; the vegetable oil-based hydrocarbon chain can also serve as an oil droplet interface recognition structure while maintaining good demulsification performance.

[0056] In Example 6, after replacing the galloyl structure with tannic acid residues, the residual petroleum content in the aqueous phase was 36 mg / L, and the thickness of the interfacial turbidity layer was 1.7 mm. The tannic acid residues contain polyphenolic hydroxyl groups, which can serve as polyphenol anchoring structures grafted onto the polysaccharide molecular chain and form multi-point contacts with gums, asphaltenes, and metal ion-associated components at the oil-water interface. This result demonstrates that polyphenol anchoring structures can be provided by different polyphenolic compounds, as long as they retain phenolic hydroxyl structures capable of participating in interfacial anchoring on the polysaccharide molecular chain, they can cooperate with zwitterionic groups and hydrophobic recognition segments to complete demulsification.

[0057] In Example 7, after replacing carboxymethyl chitosan with hydroxypropyl chitosan, the residual petroleum content in the aqueous phase was 61 mg / L, and the oil removal rate was 93.9%. Hydroxypropyl chitosan still possesses polysaccharide molecular chains, hydroxyl and amino reactive sites, and can be grafted with zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures. Compared to Example 1, the aqueous phase turbidity in Example 7 was higher, indicating that the source of the polysaccharide molecular chains and the substituent structure affect the hydration state of the backbone, the distribution of grafting sites, and bridging behavior, but do not disrupt the basic demulsifying function of the polysaccharide graft copolymer.

[0058] Example 8, by only changing the swelling and activation time, showed a residual petroleum content of 42 mg / L in the aqueous phase and an interface clearing time of 11 minutes. This result indicates that moderately extending the polysaccharide swelling and activation time does not disrupt subsequent zwitterionic grafting, hydrophobic grafting, and polyphenol grafting processes, and the resulting demulsifier can still form a stable demulsifying effect in high-salt, oily wastewater. Example 9, by only changing the zwitterionic grafting temperature, showed a residual petroleum content of 47 mg / L in the aqueous phase; Example 10, by only changing the polyphenol grafting pH, showed a residual petroleum content of 49 mg / L in the aqueous phase. These results demonstrate that the preparation method is adaptable to fluctuations in conventional processes, and the resulting polysaccharide graft copolymer can still maintain the combined structure of aqueous phase dispersion, oil-water interface migration, and interface anchoring.

[0059] In Comparative Example 1, even without the polyphenol anchoring structure, the demulsifier still contained zwitterionic groups and hydrophobic recognition segments, enabling it to maintain a certain dispersion in the high-salt water phase and enter the oil droplet interface. However, the residual petroleum content in the aqueous phase increased to 156 mg / L, and the thickness of the interfacial turbidity layer increased to 9.8 mm. This result indicates that with only the salt water dispersion structure and the hydrophobic insertion structure, it is difficult to fully disrupt the complex interfacial film formed by the associated components of colloids, asphaltenes, and metal ions. Although the oil droplets are disturbed, they still easily form a turbid transition layer. The polyphenol anchoring structure is an important structure for weakening the complex interfacial film and promoting interfacial clarification.

[0060] Comparative Example 2 used a conventional fatty alcohol polyether demulsifier. The residual petroleum content in the aqueous phase was 235 mg / L, the oil removal rate was 76.5%, and the oil-water interface clearing time was 45 minutes. Conventional fatty alcohol polyether demulsifiers mainly rely on hydrophilic and hydrophobic segments to spread at the interface. In high-salt systems, they lack polysaccharide bridging structures and polyphenol anchoring structures, as well as intramolecular zwitterionic salt-resistant structures. Therefore, they cannot simultaneously meet the requirements of high-salt dispersion, interfacial insertion, and complex interfacial film disturbance. Compared with Example 1, this comparative example showed higher aqueous phase turbidity and interfacial turbidity layer thickness, indicating that ordinary polyether-type interfacial replacement methods are insufficient for handling stable emulsion systems containing salt, colloids, and particles.

[0061] In Comparative Example 3, after raising the zwitterionic grafting temperature to 90℃, the residual petroleum content in the aqueous phase was 188 mg / L, and flocculent deposition occurred. Under these conditions, the polysaccharide molecular chains are prone to degradation, local cross-linking, or uneven grafting, resulting in unstable distribution of zwitterionic groups on the polysaccharide molecular chains. Although subsequent hydrophobic recognition segments and polyphenol anchoring structures can still be incorporated, the synergistic structure on the same molecular chain is disrupted. This result indicates that the preparation state of the zwitterionic polysaccharide intermediate directly affects the high-salt dispersion behavior and interfacial migration behavior of the final demulsifier.

[0062] In Comparative Example 4, omitting the polysaccharide swelling and activation step, the residual petroleum content in the aqueous phase was 142 mg / L, and the interfacial turbidity layer thickness was 8.6 mm. The un-swelled and unactivated carboxymethyl chitosan molecular chains had insufficient exposure of reaction sites, resulting in reduced uniformity of subsequent grafting of zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures. This led to localized aggregation and uneven interfacial interactions in the resulting product within the high-salt water phase. These results demonstrate that the swelling and activation step provides a stable foundation for polysaccharide molecular grafting and is a crucial step in preparing multifunctional demulsifiers with a single molecular chain.

[0063] As can be seen from Examples 1 to 10, when zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures are simultaneously grafted onto the polysaccharide molecular chain, the demulsifier can maintain a low residual petroleum content in the aqueous phase, a short interface clarity time, and a thin interfacial turbidity layer in high-salt oily wastewater. As can be seen from Comparative Examples 1 to 4, the absence of the polyphenol anchoring structure, the use of conventional polyether demulsifiers, deviations from suitable zwitterionic grafting temperatures, or the omission of the polysaccharide swelling and activation step all weaken at least one aspect of high-salt dispersion, interface migration, or perturbation of the composite interfacial film. The differences between the examples and the comparative examples indicate that this polysaccharide graft copolymer is not a simple superposition of zwitterionic structures, hydrophobic segments, and polyphenol structures, but rather a complete technical path that allows the above structures to work continuously in the aqueous phase and oil-water interface through the same polysaccharide backbone, forming a stable high-salt water phase, directional entry into the oil-water interface, perturbation of the composite interfacial film, and bridging of polymerized oil droplets.

Claims

1. A demulsifier for high-salt, oily wastewater, characterized in that, The invention includes polysaccharide graft copolymers, wherein the polysaccharide graft copolymers have polysaccharide molecular chains as the backbone, and the polysaccharide molecular chains are simultaneously grafted with zwitterionic groups, hydrophobic recognition segments and polyphenol anchoring structures. The zwitterionic groups include sulfobetaine groups, carboxybetaine groups, or quaternary ammonium salt-carboxylate complex groups; the hydrophobic recognition segments include aliphatic hydrocarbon chains or vegetable oil-based hydrocarbon chains; and the polyphenol anchoring structures include ortho-diol structures, galloyl structures, or tannic acid residues.

2. The demulsifier for high-salt, oily wastewater according to claim 1, characterized in that, The polysaccharide molecular chain is derived from at least one of chitosan, carboxymethyl cellulose, alginate, and starch derivatives. The polysaccharide molecular chain retains at least one of the reaction sites of hydroxyl, amino, or carboxyl groups. The zwitterionic groups, hydrophobic recognition segments, and polyphenol anchoring structures are grafted onto the reaction sites through ether bonds, amide bonds, ester bonds, or quaternization linkage structures, respectively.

3. The demulsifier for high-salt, oily wastewater according to claim 1, characterized in that, The zwitterionic group comprises a cation center and an anion center in the same side-linked branch structure. The cation center is a quaternary ammonium salt structure, and the anion center is a sulfonate or carboxylate structure. A spacer segment containing a hydroxyl or ether oxygen is disposed between the zwitterionic group and the polysaccharide molecular chain.

4. The demulsifier for high-salt, oily wastewater according to claim 1, characterized in that, The hydrophobic recognition segment is formed from fatty alcohol glycidyl ether residues, alkylamine residues, fatty acid acyl residues, or epoxidized vegetable oil ring-opening residues. The hydrophobic recognition segment and the zwitterionic group are distributed on the same polysaccharide molecular chain, and a grafting structure is formed by alternating hydrophilic and hydrophobic segments through the polysaccharide molecular chain.

5. The demulsifier for high-salt, oily wastewater according to claim 1, characterized in that, The polyphenol anchoring structure is formed by grafting tannic acid, gallic acid, catechol derivatives or dopamine derivatives. The polyphenol anchoring structure contains adjacent phenolic hydroxyl groups or multiple phenolic hydroxyl groups, and the polyphenol anchoring structure and the hydrophobic recognition segment are located together in the side chain region of the polysaccharide molecule chain.

6. The demulsifier for high-salt, oily wastewater according to claim 2, characterized in that, The polysaccharide molecular chain is a modified polysaccharide molecular chain formed by carboxymethylation, hydroxypropylation, amination or oxidation treatment. The modified polysaccharide molecular chain is provided with a first grafting site, a second grafting site and a third grafting site respectively. The first grafting site is connected to the zwitterionic group, the second grafting site is connected to the hydrophobic recognition segment, and the third grafting site is connected to the polyphenol anchoring structure.

7. The demulsifier for high-salt, oily wastewater according to claim 3, characterized in that, The spacer segment containing hydroxyl or ether oxygen is formed of glycidyl, hydroxypropyl, polyether short chain or hydroxyalkyl segment. One end of the spacer segment is connected to the polysaccharide molecular chain and the other end is connected to the quaternary ammonium salt structure. The sulfonate structure or carboxylate structure is connected to the quaternary ammonium salt structure through an alkyl linker chain.

8. The demulsifier for high-salt, oily wastewater according to claim 4, characterized in that, The hydrophobic recognition segment comprises at least one of straight-chain alkyl, branched alkyl, fatty acid unsaturated hydrocarbon chain or vegetable oil-based fatty chain, and the hydrophobic recognition segment is grafted onto the polysaccharide molecular chain through an epoxy ring-opening, amidation or esterification linking structure, wherein the grafting structure simultaneously retains hydroxyl or ether oxygen linking units.

9. A demulsifier for high-salt, oily wastewater according to claim 5, characterized in that, The polyphenol anchoring structure is connected to the polysaccharide molecular chain through amidation, Schiff base reduction, esterification or oxidative coupling. The hydrophobic recognition segment or polysaccharide backbone segment is disposed between the polyphenol anchoring structure and the zwitterionic group, and the polyphenol anchoring structure does not completely block the hydroxyl, amino or carboxyl groups on the polysaccharide molecular chain.

10. A method for preparing a demulsifier for high-salt, oily wastewater, characterized in that, include: Polysaccharide raw materials are swollen and activated to obtain polysaccharide molecular chains containing reaction sites; A zwitterionic monomer is grafted onto the polysaccharide molecular chain to form a zwitterionic polysaccharide intermediate. A hydrophobic monomer is grafted onto the zwitterionic polysaccharide intermediate to form a hydrophobically modified polysaccharide intermediate. The polyphenol compound was grafted onto the hydrophobically modified polysaccharide intermediate, and then purified and formulated to obtain the high-salt oily wastewater demulsifier.